Transition-Metal-Catalyzed Regioselective C–H Borylation of Pyridines - Sun, Qianlin; Luo, Yuncong; Xu, Xin (Synlett, 2022)
The C–H borylation strategy has spurred intense research endeavors due to the high atom- and step-economy it represents and because of the broad range of utilities of the resulting organoboranes. Nevertheless, this powerful transformation has had limited substrate scope and poor regioselectivity when it was applied to Lewis basic substrates (e.g., azines). The basic functionalities in substrates can coordinate to the metal centers, hindering the formation of products. Herein, we provide a brief overview of recent advances in transition-metal-catalyzed regioselective C–H borylation of pyridines. Attention is paid to the latest contributions, which have demonstrated remarkable regioselectivity.1 Introduction2 para-Selective C−H Borylation3 meta-Selective C−H Borylation4 ortho-Selective C−H Borylation5 Summary
Keywords: borylation; C–H activation; regioselectivity; pyridines; transition metals